Remote sensing assessment of the weed adaptability to soil salinization induced by extreme droughts on coastal agriculture - Nebojša Nikolić; Sara Cucchiaro; Eugenio Straffelini; Paolo Tarolli; Roberta Masin (iScience)
Summary: Salinization and drought pose significant challenges to agriculture in coastal regions, yet their combined impact on crop production and weed proliferation remains understudied. This study investigated the influence of salinity caused by extreme droughts on agricultural ecosystems in the Po River Delta (Italy), using remote sensing techniques and soil measurement, focusing on crop health and weed resilience. Our findings reveal that prolonged drought conditions are exacerbated by saline water intrusion and elevated soil salinity levels, particularly in fields closer to the coast. While crops, notably soybeans, exhibited susceptibility to salinity stress, weeds displayed remarkable resilience, thriving in adverse conditions and outcompeting crops. Notably, weed populations showed increased density and adaptability, even in areas of high salinity and drought. These findings underscore the urgent need for comprehensive strategies to mitigate the impact of salinity and drought on crop productivity and manage weed infestations in coastal agricultural areas.